A new approach in the assessment of motor activity in Parkinson's disease. Issue 11 (November 1991) - van Hilten, J J; Middelkoop, H A; Kerkhof, G A; Roos, R A
Abstract : Motor activity was recorded continuously with a wrist-worn activity monitor for almost six days in nine patients with different predominant manifestations of Parkinson's disease and 10 normal subjects. The indices of diurnal motor activity decreased with the progressive worsening of hypokinesia and rigidity. With this monitor and a simple diary it was possible to determine the contribution of a moderate resting tremor and choreiform dyskinesias to the motor activity level, and to monitor their variability.